Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper, 2012)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations. The level and structure of arrears to the Fund has remained broadly unchanged since the last review. Total arrears to the Fund at end-June 2012 amounted to SDR 1,302.3 million, a decline of SDR 1.6 million from the end-June 2011 level. While payments to the Fund by Sudan and Zimbabwe exceeded new obligations falling due, Somalia's arrears increased further. All overdue obligations to the Fund at end-June 2012 were due to the protracted arrears cases. Three members remain in protracted arrears to the Fund-Somalia, Sudan, and Zimbabwe. Sudan accounted for the bulk of the arrears to the Fund (76 percent).